(untitled) (Damu Journal of Sport Sciences, 2024)
The skill of sending in volleyball is a major means of obtaining points, while the skill of receiving the serve is an important defensive skill, as it is used to receive the sent balls. Therefore, mastering the skill of receiving is of utmost importance, as any mistake made by the receiving player may lead to the loss of points. As for reinforcement feedback, it is classified based on what it provides to the learner or coach, as the learner obtains knowledge about the results of his performance. The research community was chosen intentionally, as the research sample represents the entire original community, which consists of 24 players from the Al-Sudair Girls' Intermediate School team in the Third Rusafa Education Directorate. The main research sample consisted of 20 players. Tests were conducted for both the experimental and control groups, and the results were in favor of the experimental group. Post-tests were also conducted for the two groups, which also showed the superiority of the experimental group. The conclusions indicate that skill exercises have a positive effect on learning the skills of sending and receiving in volleyball, and the educational units achieved a noticeable development. In addition, the exercises were appropriate for the ages of the players.